The IMF to the rescue: did Greece benefit from the fund's experience in dealing with highly indebted countries?. Issue 4 (2nd October 2019) - Dullien, Sebastian; Fritz, Barbara; Mühlich, Laurissa
Abstract : The paper analyses how the IMF brought its experience concerning the distinction between liquidity and solvency crises and their adequate handling gained during earlier crises into the troika's approach to Greece. We link multiple equilibria models with the IMF's experience gained in Latin America in the 2000s and subsequent changes in the IMF's policy guidelines. We show that the IMF changed its approach after the Argentinian crisis but ignored some of these insights in the case of Greece. Hence, we argue that the inclusion of the IMF in Europe's crisis-fighting did not completely deliver what had been hoped for.